The Relationship between the Restorative Perception of the Environment and the Physiological and Psychological Effects of Different Types of Forests on University Students - Qiaohui Liu (MDPI AG, 2021)
Short-term exposure to a forest environment is beneficial to human physiological and psychological health. However, there is little known about the relationship between the restorative perception of environment and physiological and psychological restoration achieved by experiencing the forest environment. This study evaluated the relationship between the restorative perception of different types of forests and human physiological and psychological effects. A sample of 30 young adult students from Beijing Forestry University was exposed to coniferous, deciduous, and mixed forests as well as an urban site. Restorative perception of the environment was measured using the PRS questionnaire. Restorative effects were measured using physiological indicators (blood pressure and heart rate) and three psychological questionnaires (Restorative Outcome Scale; Subjective Vitality Scale; Warwick–Edinburgh Mental Well-being Scale). The results demonstrated the following: (1) There were significant differences in the perceived restorative power of the three types of forests, with the highest level in the mixed forest, followed by the coniferous forest and the deciduous forest. (2) All types of forests were beneficial to physiological and psychological restoration. The mixed forest had the greatest effect in lowering blood pressure and heart rate as well as increasing vitality, while the coniferous forest had the strongest increases in psychological restoration and positive mental health. (3) The level of perceived restorative power of environment was positively related to the physiological and psychological restoration. These findings provide practical evidence for forest therapy that can maximize the restorative potential of forests.